KOMPETENSI PEDAGOGIK GURU DALAM IMPLEMENTASI MODEL PEMBELAJARAN INOVATIF - Syunu Trihantoyo; Ayu Wulandari; Milla Uzlifatul Janah; Mala Nur Kumairo; Deyah Nur Alfi (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Pedagogic Competence is the study of Education. Pedagogic Science learns about an ability (expertise) that must be possessed by teachers in the form of the ability to understand students, what methods are appropriate for establishing communication with students, what techniques are used in preparing Learning Designs for students, how to implement learning evaluation, etc. The problem examined in this study is what learning model is designed by the teacher so that students at SDN Sepanjang 2 do not feel bored with the subject matter being directed. Delivering creative, innovative and fun learning materials will make the class atmosphere less saturated, this will make students able to receive lessons easily. The purpose of this research is to see how far the creativity of teachers at SDN Sepanjang 2 develops in delivering material to their students. In the Implementation of Pedagogic Competency schools must provide facilities in the form of adequate facilities and infrastructure so that teachers can optimize the implementation of Pedagogic Competency activities. The research method used in this research is descriptive qualitative method.